A pilot study of the quality of informed consent materials for Aboriginal participants in clinical trials. Issue 8 (2nd August 2005) - Russell, F M; Carapetis, J R; Liddle, H; Edwards, T; Ruff, T A; Devitt, J
Abstract : Objective: To pilot informed consent materials developed for Aboriginal parents in a vaccine trial, and evaluate their design and the informed consent process. Methods: Cross sectional quantitative and qualitative survey of 20 Aboriginal and 20 non-Aboriginal women in Alice Springs. Information about the proposed research was presented to Aboriginal participants by an Aboriginal researcher, using purpose designed verbal, visual, and written materials. Non-Aboriginal participants received standard materials developed by the sponsor. Questionnaires were used to evaluate recall and understanding immediately and five days later. Qualitative analysis of Aboriginal participants' interviews was performed. Results: There were no differences between the groups in understanding of diseases prevented by the vaccine, the potential risks of participating, or the voluntary nature of participation. Most Aboriginal participants had difficulty with the concept of a "licensed" versus "unlicensed" vaccine. The non-Aboriginal group had a good understanding of this. Aboriginal participants identified the use of the flipchart, along with a presentation by a doctor and Aboriginal health worker, as preferred delivery modes. Group presentations were preferred rather than one-on-one discussions. The use of the questionnaire posed considerable methodological difficulties. Conclusions: A one-off oral presentation to Aboriginal participants is unlikely to produce "informed consent". Key but unfamiliar concepts require identification and particularly considered presentation.